TRANSFER PRICING MULTINATIONAL COMPANIES IN INDONESIA: THE ROLE OF GOOD CORPORATE GOVERNANCE (GCG), TUNNELING INCENTIVE AND LEVERAGE - Marheni Marheni; Yunita Maharani; Liya Ermawati (Integrated Journal of Business and Economics (IJBE), 2022)
The aims of study were 1) to analyze the effect of Good Corporate Governance (GCG) on transfer pricing; 2) Analyzing the effect of tunneling incentive on transfer pricing and 3) Analyzing the effect of leverage on transfer pricing. The research population were multinational companies in the manufacturing sector in Indonesia at 2010-2019. Methods of analysis used multiple regression analysis. The results showed that 1) GCG had a positive and significant effect on the company's transfer pricing. Hypothesis H1 which states that GCG had a positive effect on the company's transfer pricing is proven: 2) Tunneling Incentive (TI) had a positive and significant effect on the company's transfer pricing. Hypothesis H2 which states that Tunneling Incentive (TI) had a positive effect on the company's transfer pricing is proven; 3) Leverage had not positive and significant effect on the company's transfer pricing. Hypothesis H3 which states that leverage has a positive effect on the company's transfer pricing is not proven.